Power and Conflict in the Age of Transparency
XI, 371 p.
Keywords: The twenty-first century will feature unprecedented global transparency. From the advent of the Internet to the rise of global media to the proliferation of commercial satellites, more information will be available to more people about more things than ever before in human history. This increase in transparency is certain to have a major effect on international politics, and particularly on the possibility of armed conflict in the next millennium. This volume represents the first comprehensive collection of articles written by leading scholars and policy analysts examining the effects of transparency on world politics.